Discursive Institutionalism and Food Policy Research: The Case Study of Canada’s National Food Policy - Coulas, Mary (Frontiers in Communication, 2021)
“Food” and “policy” are ambiguous concepts. In turn, the study of food policy has resulted in varying approaches by different disciplines. However, the power behind the discursive effects of these concepts in policymaking—how food policy is understood and shaped by different actors as well as how those ideas are shared in different settings—requires a rigorous yet flexible research approach. This paper will introduce the contours of discursive institutionalism and demonstrate methodological application using the case study example of Canada’s national food policy, Food Policy for Canada: Everyone at the Table! Selected examples of communicative and coordination efforts and the discursive power they carry in defining priorities and policy boundaries are used to demonstrate how discursive institutionalism is used for revealing the causal and material consequences of food policy discourses.